Caulis Sargentodoxae Prescription Plays a Therapeutic Role with Decreased Inflammatory Cytokines in Peritoneal Fluid in the Rat Endometriosis Model. (29th May 2020) - Zhuang, Mengfei; Cao, Yang; Shi, Yan; Yu, Lin; Niu, Yanan; Zhang, Tingting; Sun, Zhaogui
Abstract : Caulis Sargentodoxae prescription has been confirmed by the gynecological clinical observation to be effective in the treatment of endometriosis (EMs), and inflammatory cytokines were involved in EMs. In this paper, animal experiments were designed to explain anti-inflammatory mechanisms of Caulis Sargentodoxae prescription on endometriosis. The EMs model was established by autoplastic transplantation, and rats were randomly divided into seven groups: normal control group, model group, ovariectomized group, gestrinone (Western medicine) group, Caulis Sargentodoxae prescription (Chinese medicine) group, celecoxib (inhibitor) group, and combination (Chinese medicine + inhibitor) group. After oral administration for 21 days, the growth inhibitory rates of the ectopic endometria in treatment groups were evaluated, and the levels of inflammatory cytokines in the serum and peritoneal fluid were determined by ELISA, as well as the expression of prostaglandin endoperoxide synthase 2 (PTGS2) in the ectopic endometrial tissues was detected by real-time polymerase chain reaction, immunohistochemistry, and western blotting. The growth inhibitory rates of the ectopic endometria were significantly higher in the Caulis Sargentodoxae prescription group and gestrinone group, in comparison with the model group p < 0.05 . In the Caulis Sargentodoxae prescription group, the levels of inflammatory cytokines including IL-1, IL-2, IL-6, TNF- α, and PGE2 were all reduced in the serum and peritoneal fluid p < 0.05 . In addition, the specific expression of PTGS2 in the ectopic endometrial tissues significantly decreased in the Caulis Sargentodoxae prescription group and PTGS2 inhibitor celecoxib group both at mRNA and protein levels, but in the steroid hormone drug gestrinone group not at the mRNA level. So, Caulis Sargentodoxae prescription has a reliable therapeutic effect on the EMs by its comprehensive anti-inflammatory roles, possibly in a way different from gestrinone.